2020
DOI: 10.1021/acsanm.0c01177
|View full text |Cite
|
Sign up to set email alerts
|

Monolayer Assembly of MultiSpiked Gold Nanoparticles for Surface-Enhanced Raman Spectroscopy-Based Trace Detection of Dyes and Explosives

Abstract: For sensitive and reproducible surface-enhanced Raman scattering (SERS)-based trace detection, a SERS platform with high concentration of homogeneously distributed hotspots is needed. Herein, we report a facile monolayer assembly of multispiked gold nanoparticles (MSGNPs) of various sizes over a large area. The assembly was achieved simply by tuning the concentration of MSGNPs in a suspension and subsequently drying it on a substrate under ambient conditions. A monolayer assembly for MSGNP sizes ranging from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…Therefore, sensitive detection of pigments and melamine is very promising for health and safety applications. 30 …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, sensitive detection of pigments and melamine is very promising for health and safety applications. 30 …”
Section: Resultsmentioning
confidence: 99%
“…For reproducible SERS-based trace molecule detection, we have developed facile synthesis methods of metal nanostructures that ensure highly concentrated hotspots and uniform distribution on the substrate. Firstly, we demonstrated a size-controlled synthesis of multi-spiked gold NPs (MSGNPs) that can be assembled into monolayers over a centimeter length scale simply by drying the suspension on a substrate under ambient conditions 6 . MSGNPs were synthesized by seed-mediated synthesis and our different seed concentrations were added under vigorous stirring, then samples were labeled as from P1 to P4.…”
Section: Methodology Results and Discussionmentioning
confidence: 99%
“…[37] Many studies evaluated the reproducibility of the substrate by randomly selecting several points on one substrate and collecting signals for comparison. [28,38] Actually, these evaluation results reflect only the uniformity from spot to spot, but not the reproducibility from substrate to substrate. Here, we randomly selected 20 points in substrate M and substrate N from the same batch, respectively, and found that the integral areas under the curve of the characteristic peak 1,570 cm À1 were highly consistent (Figure 3a).…”
Section: Uniformity and Reproducibility Of Au Nss Sammentioning
confidence: 99%
“…In many studies, the analyte solution was dropped on the substrate and detected after drying. [14,15,28] In this case, coffee ring of the analyte will also be formed, leading to uneven distribution of analyte molecules and inaccurate determination of the concentration. [29] In this study, we employed the classic Langmuir-Blodgett (LB) technique [30] to form a SAM of gold nanostars (Au NSs) at the water oil two-phase interface and then transferred the SAM onto silicon wafers as SERS substrates (Scheme 1).…”
mentioning
confidence: 99%